EKSISTENSI BECAK VESPA DI KOTA PADANGSIDIMPUAN DALAM FOTOGRAFI DOKUMENTER - Yoga Rahim Batubara; Shofi Nurhayati (STKIP Subang, 2026)
Vespa pedicabs (Becak Vespa) represent a cultural transportation icon as well as a visual identity deeply embedded in the cultural landscape of Padangsidimpuan City. However, in recent years, the existence of this traditional mode of transportation has faced a severe threat of extinction due to the disruption of app-based ride-hailing services, scarcity of spare parts, and the phenomenon of fleet ownership transfer to collectors from outside the region. This art creation research aims to visualize the remaining existence, living spaces, and socio-economic struggles of Vespa pedicab drivers and mechanics in Padangsidimpuan City through the medium of documentary photography. The method employed in this creation is a qualitative method with a documentary photography approach, utilizing the photo story model. This approach is applied to construct a profound visual narrative regarding the daily realities of the subjects. The outcome of this artistic creation is a series of documentary photographs that not only capture the visual aesthetics of the modified vehicles but also function as a socio-historical document and a visual archive of the sociological dynamics of urban society in Padangsidimpuan. This work is expected to serve as a medium for reflection as well as an effort to preserve the collective memory of society regarding the existence of Vespa pedicabs, which are increasingly marginalized by the currents of modernization.